2020
DOI: 10.1111/cei.13437
|View full text |Cite
|
Sign up to set email alerts
|

The effects of advanced maternal age on T-cell subsets at the maternal–fetal interface prior to term labor and in the offspring: a mouse study

Abstract: Summary Women who conceive at 35 years of age or older, commonly known as advanced maternal age, have a higher risk of facing parturition complications and their children have an increased risk of developing diseases later in life. However, the immunological mechanisms underlying these pathological processes have yet to be established. To fill this gap in knowledge, using a murine model and immunophenotyping, we determined the effect of advanced maternal age on the main cellular branch of adaptive immunity, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 175 publications
(264 reference statements)
0
11
1
Order By: Relevance
“…As described above, AMA is associated with increased delivery complications and perinatal mortality as well as with reduced body weight at birth [33,38], which per se are known risk factors for adult diseases [15]. Available data on postnatal development indicate an increased risk of cardio-metabolic and neurological disorders in AMA offspring [32,33,38,39,41,42]. Some authors reported that AMA offspring displayed high blood pressure, indicative of predisposition to cardiovascular diseases [32].…”
Section: Postnatal Development Behavior and Health Of Mouse Offspring Conceived By Aged Mothersmentioning
confidence: 99%
See 4 more Smart Citations
“…As described above, AMA is associated with increased delivery complications and perinatal mortality as well as with reduced body weight at birth [33,38], which per se are known risk factors for adult diseases [15]. Available data on postnatal development indicate an increased risk of cardio-metabolic and neurological disorders in AMA offspring [32,33,38,39,41,42]. Some authors reported that AMA offspring displayed high blood pressure, indicative of predisposition to cardiovascular diseases [32].…”
Section: Postnatal Development Behavior and Health Of Mouse Offspring Conceived By Aged Mothersmentioning
confidence: 99%
“…Decline of female reproductive functions over time is characterized by a decrease in oocyte reservoir, low oocyte quality and high risk of pregnancy loss or complications, as widely described in several mammalian species [31][32][33][34][35][36][37][38][39][40]. Mouse models showed that aged females (> 10 months old) are able to produce progeny, however pregnancies are characterized by smaller litter size and increased rate of complications/pregnancy lost when compared to pregnancy outcome in young females [32][33][34].…”
Section: Early Development and Reproductive Outcome In Pregnancies At Advanced Maternal Agementioning
confidence: 99%
See 3 more Smart Citations